P‐99: Occluded Three‐dimensional Object Display Algorithm Using Fourier Spectrum in Integral Imaging. Issue 1 (May 2017) - Xing, Yan; Xiong, Zhao-Long; Deng, Huan; Wang, Qiong-Hua
Abstract : We propose an occluded three‐dimensional (3D) object display algorithm based on Fourier Spectrum in integral imaging (II). The orthographic sub‐images are achieved by acquiring their Fourier spectrums. Based on the recovered sub‐images, the II reconstruction is used to display the 3D object without occlusion effect. Experimental results verify the effectiveness of the proposed algorithm in II display.